PENGARUH MODEL PEMBELAJARAN SYNECTIC MELALUI TEKNIK IMAJINASI TERHADAP KEMAMPUAN MENULIS PUISI SISWA KELAS V SD NEGERI PANNYIKKOKANG II KECAMATAN PANAKKUKANG KOTA MAKASSAR - Debhy Marekana; Nurhaedah; Rifhani handayani L (STKIP Subang, 2026)
This research is motivated by the problem of students' lack of poetry writing skills. The objectives of this study are: 1. To determine the process of implementing the synectic learning model using imagination techniques among fifth-grade students of Pannyikkokang II Public Elementary School, Panakkukang District, Makassar City. 2. To determine the level of poetry writing skills among fifth-grade students of Pannyikkokang II Public Elementary School, Panakkukang District, Makassar City. 3. To determine the effect of the synectic learning model using imagination techniques on the poetry writing skills of fifth-grade students of Pannyikkokang II Public Elementary School, Panakkukang District, Makassar City. This study uses a quantitative approach with a quasi-experimental research design of the nonequivalent control group design type. The sample in this study was 23 fifth-grade students of Pannyikkokang II Elementary School, Panakkukang District, Makassar City. The determination used a purposive sampling technique with class V A as the experimental class and class V B as the control class. The data analysis technique used was descriptive statistical analysis and inferential statistics using the Independent sample t-test. The results of the experimental class study 1) the application of the learning process with the synectics learning model was carried out quite well at the first meeting, the second meeting was in the very good category, 2) The ability to write poetry after the application of the synectics learning model showed an increase, this was evidenced by the posttest score being higher than the pretest score, 3) The synectics learning model influenced the poetry writing ability of fifth-grade students of Pannyikkokang II Elementary School, Panakkukang District, Makassar City. So it can be concluded that the synectics learning model through this imagination technique has a significant effect on the ability to write poetry.